Direct Virtual Power Control - Li Xiang; Han Minxiao (Institute of Advanced Engineering and Science, 2014)
A direct virtual power control algorithm is presented in this paper for VSC-HVDC startup. This control algorithm is based on direct power control (DPC) and expands the range of DPC. When the VSC converter AC side open circuit or the AC side current is zero, the control algorithm maintains the DPC feedback loop by introducing a virtual power, so that the DPC is able to control the AC output voltage amplitude and frequency stability before the VSC converter connecting to the grid network and keep consistent with the grid connection point. This algorithm process is simple, containing most of the DPC control module, and consistent with the DPC structure. Therefore, the control algorithm switches smoothly before and after the VSC converter connecting to the grid. This paper uses PSCAD / EMTDC software platform and laboratory hardware circuit experiments to test and verify the correctness and validity of the control algorithm.